Epigenetic pharmaceuticals used in the clinic - Paul, Thomas (Henry Stewart Talks, 2020)
Epigenetic drugs in chemotherapy, Selecting patients for epigenetic therapy, Side effects of epigenetic agents, Unique therapeutic mechanisms of epigenetic treatments, How is epigenetic therapy applied?, Haematological vs solid tumours, Drug resistance